Analysis of village financial management on financial performance with regulatory changes as intervening variables - Harun Blongkod; Herlina Rasjid (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to determine and analyze Village Financial Management on Financial Performance with Regulatory Changes as Intervening Variables (Study in Villages throughout the Paguyaman Pantai District, Boalemo Regency, Gorontalo Province). The population of this research is Village Apparatus who work in the Village Government and based on the sample criteria are the Village Head, Village Secretary, Village Administration Midwife, Village Economic Sector, Treasurer, Head of BPD, Deputy Chairperson of BPD, Secretary of BPD, LPM, Chairperson of Youth Organizations and Head of Dusun /Environment, totaling 107 respondents. The test was carried out using a descriptive analysis method using Structure Equation Modeling with the help of the AMOS 24.0 program. This research proves that village financial management has a positive and significant effect on financial performance. Village financial management has a positive and significant effect on regulatory changes. Regulatory changes have a positive and significant effect on financial performance. Village financial management has a positive and significant impact on financial performance through regulatory changes in villages throughout the Paguyaman Pantai sub-district, Boalemo Regency, Gorontalo Province.